Rare-Earth-Catalyzed Hydrosilylation and Dehydrogenative Coupling of Hydrosilanes - Chen, Wufeng; Li, Jianfeng; Cui, Chunming (Synlett, 2020)
Activation of Si–H bonds with rare-earth complexes could generate the highly reactive rare-earth hydrides or silyl complexes, which are key intermediates for hydrosilylation and cross-coupling reactions. This Account summarizes the recent advances in the rare-earth-catalyzed hydrosilylation of unsaturated substrates and dehydrogenative coupling of hydrosilanes with amines in our laboratory. The results demonstrated that rare-earth catalysts are unique in their reactivity and selectivity, enabling some unprecedented reactions.1 Introduction2 Dehydrogenative Coupling of Hydrosilanes with Amines3 Catalytic Dehydrogenative Coupling of Hydrosilanes with Amines4 Catalytic Hydrosilylation of Terminal Alkenes and Polymerization of Styrene5 Catalytic Hydrosilylation of Internal Alkenes6 Catalytic Dihydrosilylation of Internal Alkynes7 Conclusions and Outlook
Keywords: rare-earth metal; hydrosilane; activation; catalysis; mechanism